(untitled) (Ameghiniana, 2014)
Approximately seventy specimens of Sahnipushpam deposited at the repository of the Birbal Sahni Institute of Palaeobotany, Lucknow were studied. It was observed that the flower was described upside down by the earlier workers. The receptacle designated by them is in fact the upper part of the multilocular ovary, the basal part of hypanthium is lysigenous and without any vascular supply should also be the upper part. Structures previously interpreted as stamens are actually lacerated lower parts of the hypanthium. The pollen grains described previously are not in situ but fungal spores. The presence of bracts surrounding the peltate plate could only be explained by assuming that these were the basal part of the flower. In view of these observations, Sahnipushpam is emended here to accommodate the female flower and the post fertilized ovary in various stages of fruit formation.